Teachers’ Strategies in Enhancing Numeracy Skills in Elementary Schools - Minati Rina Hardiyana; Sintha Sih Dewanti; Abroto; Suwardi (Doctoral Program In Elementary Madrasah Teacher Education Faculty Of Tarbiyah And Education - UIN Sunan Kalijaga Yogyakarta, 2026)
Numeracy skills are essential competencies that every student must possess. However, results from international assessments such as PISA indicate that Indonesian students' numeracy literacy remains relatively low, necessitating more effective instructional strategies. This study aims to identify and analyze various strategies employed by teachers to enhance elementary students’ numeracy literacy through a literature review approach. The method used is a content analysis-based literature review focusing on publications from the last ten years. The literature search was conducted systematically using several reputable academic databases, including Scopus, ScienceDirect, SpringerLink, and Google Scholar. Keywords used in the search included: teacher strategies, numeracy literacy, elementary mathematics education, numeracy pedagogy, elementary education, and teacher practice in numeracy. The findings indicate that strategies such as blended learning, Realistic Mathematics Education (RME), problem-based learning (PBL), differentiated instruction, and game-based learning consistently have a positive impact on improving students’ numeracy literacy. These strategies support learning processes that are more adaptive, contextual, and engaging, while effectively fostering students’ critical thinking, collaboration, and problem-solving skills.